2020
DOI: 10.1007/s13300-020-00950-7
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Open-Label Short-Term Pilot Study on Modification of the Skin Hydration Status During Treatment With a Sodium-Glucose Cotransporter-2 Inhibitor

Abstract: Introduction: Various types of skin lesions with pruritus have been reported in participants of Asian clinical trials on sodium-glucose cotransporter-2 (SGLT2) inhibitors. The aim of this study was to determine whether the diuretic effect of a SGLT2 inhibitor could modify skin hydration status in patients with type 2 diabetes mellitus. Methods: A prospective, short-term, open-label, two-parallel-arm, pilot study was conducted. Eligible patients were assigned to either a SGLT2 inhibitor (50 mg ipragliflozin onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…First, as SGLT2i treatment, may alter the sodium and water content through diuresis, we hypothesize that it could lead to skin dehydration, xerosis, pruritus and skin inflammation 33,34 . However, recent studies have shown that SGLT2i treatment reduced only the cutaneous sodium content and not the hydration status 35,36 . In addition, another study by Maifeld et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, as SGLT2i treatment, may alter the sodium and water content through diuresis, we hypothesize that it could lead to skin dehydration, xerosis, pruritus and skin inflammation 33,34 . However, recent studies have shown that SGLT2i treatment reduced only the cutaneous sodium content and not the hydration status 35,36 . In addition, another study by Maifeld et al .…”
Section: Discussionmentioning
confidence: 98%
“…33,34 However, recent studies have shown that SGLT2i treatment reduced only the cutaneous sodium content and not the hydration status. 35,36 In addition, another study by Maifeld et al found that the cutaneous sodium content was elevated in patients with psoriasis and could be a potential marker for disease severity. 37 Thus, reducing the cutaneous sodium level after SGLT2i treatment, may conversely indicate a beneficial role for SGLT2i therapies in psoriasis.…”
Section: Discussionmentioning
confidence: 99%